AN ANALYSIS OF INFLUENCED FACTORS OF LOCAL RESIDENTS’ PARTICIPATION IN TOURISM DEVELOPMENT: BINH THUY DISTRICT, CAN THO CITY, VIETNAM - Mai, Thị Kiều Lan (IKSAD Publishing House, 2025)
The objective of this article is to examine the factors involving local residents' involvement in the process of tourism development. By utilizing field surveys, questionnaires distributed among local residents, and applying Exploratory Factor Analysis (EFA) to the collected data from Binh Thuy district in Can Tho city, Vietnam, several significant factors have been identified. The research outcomes highlight five key factors that play a role in residents' participation including household resources, residents' perception about tourism, local policies, benefits from residents’ participation in tourism, and local resources. Drawing upon these identified factors, the article puts forward various solutions to enhance the level of residents' participation in the future